Deep end [large type] - Hazelwood, Ali (Thorndike Press large print romance series., 2025)
"A competitive diver and an ace swimmer jump into forbidden waters in this steamy college romance from the New York Times bestselling author of The Love Hypothesis. Scarlett Vandermeer is swimming upstream. A junior at Stanford and a student-athlete who specializes in platform diving, Scarlett prefers to keep her head down, concentrating on getting into med school and on recovering from the injury that almost ended her career. She has no time for relationships--at least, that's what she tells herself. Swim captain, world champion, all-around aquatics golden boy, Lukas Blomqvist thrives on discipline. It's how he wins gold medals and breaks records: complete focus, with every stroke. On the surface, Lukas and Scarlett have nothing in common. Until a well-guarded secret slips out, and everything changes. So they start an arrangement. And as the pressure leading to the Olympics heats up, so does their relationship. It was supposed to be just a temporary, mutually satisfying fling. But when staying away from Lukas becomes impossible, Scarlett realizes that her heart might be treading into dangerous water..."--